Self-Regulated Learning Strategies in The Subject of Akidah Akhlak to Reduce Academic Procrastination - Raniya, Pudyas Tataquna; Maknin, Nur Afifah Khurin; Silmi, Thoriq Aji; Widodo, Hendro (Universitas Islam Sultan Agung, 2025)
This study aims to explore strategic self-regulated learning in Akidah Akhlak learning to reduce academic procrastination among students. Academic procrastination is a significant problem faced by many students, which can have a negative impact on learning achievement and psychological health. Data shows that around 50% of college students experience procrastination in completing academic tasks, often caused by factors of perceived ability and emotional distress. This research involved students at Aisyiyah Unggulan Junior High School in Bantul, Yogyakarta, using qualitative methods and data collection techniques through observation, interviews, and documentation. The results showed that Akidah Akhlak learning plays an important role in instilling the values of discipline and responsibility, as well as teaching effective self-management strategies. Despite the progress, some students still have difficulties in implementing those values in daily practice, which emphasizes the need for a more systematic approach in education. This study recommends better integration between self-regulated learning strategies and the Akidah Akhlak curriculum to help students manage their academic tasks and reduce the level of procrastination